Transient Neonatal Myasthenia Gravis: A Case Report - Sanja Ristovska; Stomnaroska Orhideja; Renata Dimitrioska (Macedonian Academy of Science and Arts/Sciendo, 2023)
Transient neonatal myasthenia gravis (TNMG) is a neuromuscular disorder that occurs in infants born from mothers with myasthenia gravis (MG) due to transplacental transfer of antibodies against the acetylcholine receptor. TNMG is a rare form occurring in 10-15% of infants born from mothers with MG. We present a case of a newborn with TNMG with generalized hypotonia and respiratory distress. The newborn shows symptoms of hypotonia, weakened reflexes, poor crying, difficult sucking and potentiated tachydyspnea after 24 hours of birth and needs of assisted mechanical ventilation. Based on the mother's positive history of MG and the high titer of mother's (8.43nmol/l) and newborn's (9.088nmol/l) anti-AChR antibodies, TNMG was diagnosed. The baby was treated with assisted mechanical ventilation and neostig-mine until the anti-AChR antibody titer was negative. Adequate management of the newborn resulted in a positive outcome and evident withdrawal of the symptoms. Although TNMG is one of the rare neuromuscular disorders in newborns that can be treated, a multidisciplinary approach in the management of pregnant women with MG and newborns through timely diagnosis and early appropriate treatment, results in successful resolution of this condition.
Keywords: transient neonatal myasthenia gravis; neostigmine; myasthenia gravis; hypotonia